Light induced catalytic intramolecular hydrofunctionalization of allylphenols mediated by porphyrin rhodium(iii) complexes. Issue 34 (2nd August 2016) - Liu, Xu; Wang, Zikuan; Fu, Xuefeng
Abstract : Catalytic intramolecular hydrofunctionalization of allylphenols to heterocyclic compounds mediated by rhodium(iii ) porphyrin complexes was described. Abstract : Catalytic intramolecular hydrofunctionalization of allylphenols to heterocyclic compounds mediated by rhodium(iii ) porphyrin complexes was described. The Wacker-type intermediate β-heterocyclic alkyl rhodium complex was independently synthesized and crystallized.